Studi Kritis Bahan Ajar Mata Pelajaran Haji dan Umrah Kelas IX SMP PGRI Bencoy Kec. Cireunghas Sukabumi - Hoerul Kusban; Siti Qomariyah; Atep Abdurohman; Ridwan Hermawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The low level of students’ understanding of religious practices and Islamic values in daily life poses a significant challenge in teaching Islamic Religious Education (PAI). In the topic of “Hajj and Umrah” for Grade IX students at SMP PGRI Bencoy, Cireunghas District, Sukabumi, the learning process plays a vital role in shaping Islamic character and instilling noble morals. This subject not only emphasizes theoretical knowledge but also promotes a deeper understanding of the procedures for performing Hajj and Umrah in accordance with Islamic law. This study aims to critically analyze the learning objectives, content, methods, evaluation, references, and teaching materials used by teachers in the instructional process. A qualitative approach was employed, with data collected through classroom observations, interviews with teachers and students, as well as an analysis of learning documents. The findings reveal that PAI instruction on the topic of Hajj and Umrah is aligned with the basic competencies and curriculum requirements. However, shortcomings remain in the relevance of the material to real-life contexts, the limited use of technological media, and the less-than-optimal assessment of affective and psychomotor domains. Strengthening students’ understanding of Islamic teachings in their daily lives is essential for developing a holistic Islamic personality. Overall, while the teaching materials are relatively appropriate, further development is needed to make them more applicable, contextual, and impactful in enhancing students’ comprehension and practice of Islamic teachings in everyday life.